2015
DOI: 10.3390/toxins7030728
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Deoxynivalenol Content in Grain, Chaff, and Straw with Fusarium Head Blight Severity in Wheat Varieties with Various Levels of Resistance

Abstract: A total of 122 wheat varieties obtained from the Nordic Genetic Resource Center were infected artificially with an aggressive Fusariumasiaticum strain in a field experiment. We calculated the severity of Fusarium head blight (FHB) and determined the deoxynivalenol (DON) content of wheat grain, straw and glumes. We found DON contamination levels to be highest in the glumes, intermediate in the straw, and lowest in the grain in most samples. The DON contamination levels did not increase consistently with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…Agric. v.75, n.5, p.426-431, September/October 2018 component of the breeding selection criteria (Arseniuk et al, 1999;Ji et al, 2015;Jin et al, 2014;Schlang and Duveiller, 2012). To overcome the high costs associated with mycotoxin analysis, assessments of FDK, in addition to being a more affordable method, usually correlate more strongly with mycotoxin levels than visual assessment of the wheat spikes, and could be used as a surrogate variable to select for resistance to mycotoxin (Mesterházy et al, 2005;Sneller et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Agric. v.75, n.5, p.426-431, September/October 2018 component of the breeding selection criteria (Arseniuk et al, 1999;Ji et al, 2015;Jin et al, 2014;Schlang and Duveiller, 2012). To overcome the high costs associated with mycotoxin analysis, assessments of FDK, in addition to being a more affordable method, usually correlate more strongly with mycotoxin levels than visual assessment of the wheat spikes, and could be used as a surrogate variable to select for resistance to mycotoxin (Mesterházy et al, 2005;Sneller et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the latter two mycotoxins, the correlation coefficient was close to unity (0.931-0.932). According to Waśkiewicz et al (9), Zhang et al (56), and Ji et al (57), mycotoxin content in grain positively correlates with the severity of FHB. By contrast, Lacey et al (58) reported the presence of DON in grain with no macroscopic symptoms of FHB or grain colonisation by Fusarium spp.…”
Section: Coefficients Of Correlationmentioning
confidence: 99%
“…F. culmorum isolates show high levels of phenotypic and genotypic variability in culture, including colony morphology, pigmentation and sporulation (Puhalla 1981; Kollers et al 2013; Miedaner et al 2013). In addition, variation in aggressiveness and mycotoxin production have been found among various isolates that were collected from different geographic locations (Gang et al 1998; Berna et al 2012; Winter et al 2013; Fang et al 2015).…”
Section: Introductionmentioning
confidence: 99%